APLIKASI PENJUALAN ALAT NAVIGASI DAN KOMUNIKASI KAPAL DENGAN MENGGUNAKAN METODE MDLC BERBASIS ANDROID - Saputra, Dedy; Putri, Anggia Dasa (LPPM Universitas Putera Batam, 2023)
At this time it is full of the use of technology everywhere that makes it easier to do everything, tools that support things like that, such as cellphones, computers, the internet and so on. Through this technology someone can easily find the various information they need. In the world of shipping, many need navigation and communication tools for their ship's needs and for that they will go to places that sell these tools to find ship equipment, ship navigation and communication tools consist of several types, namely Navigation Equipment consisting of Radar, Echo Sounder, AIS (Automatic Identification System), Gps and others that must be owned by every ship because it is really needed to help the ship's journey as well as communication tools that must be owned by a ship consisting of VHF Radio, VHF Radio, Satellite Phone, Marine VHF Radio and others that are used to communicate with each other for use by ship people. So, to make it easier to find and buy ship equipment, a technology called a sales application is needed. In this scientific work, the aim is to design a system for customers based on Android, Android is an operation that runs on cellphones and has been widely used by teenagers to adults, but Android is more in demand by many users compared to IOS because the PlayStore application on Android has many application options. The software used in making this system uses the MDLC method, and the results in making this android-based application make the application easy to access for users as well as the application for selling ship navigation and communication tools designed with an attractive appearance and utilizing a media of images, videos that are will increase the level of knowledge of the shipyard. Keywords:, Android, Multimedia Development Life Cycle.